A framework for analysing the individual capital of travel vloggers - Made Handijaya Dewantara; Xin Jin; Sarah Gardiner (Annals of Tourism Research Empirical Insights, 2025)
This study employs an individual capital theoretical framework to analyse travel vlogs and identify ways to maximise vlog performance success. The first phase analyses the social media content of ten vlogs and their viewer comments (n~=~816). This was followed by a second phase comprising in-depth interviews with ten viewers and ten destination marketers to validate and re-evaluate the initial findings. Thematic analysis of the vlogs reveals six attributes of individual capital. This study extends the theory of individual capital within the context of destination marketing and travel vlogging by detailing each attribute and identifying a new one.
Keywords: 330; Destination marketers; Destination marketing; Individual capital; Social media; Travel vlog